PENGARUH BUDAYA ORGANISASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN ( Studi Kasus Pada Karyawan Bagian Produksi PT. Delta Merlin Dunia Textile IV) - Nikho Ardhyanto; Apriatni Endang Prihatini; Bulan Prabawani (Universitas Diponegoro, 2015)
Employee performance is a benchmark in the business of a company to achieve its objectives.Employees play a role in running the various operations of the company which will affect the company'ssuccess in achieving its objectives. Organizational culture and compensation have a role in improving theperformance of employees. Therefore, two things need to be considered in improving the performance ofemployees of PT. Textile World Merlin Delta IV. Organizational culture and compensation have an influenceeither directly or indirectly in improving employee performance. This study aims to determine the influenceof organizational culture on employee performance and compensation of the production of PT. Delta MerlinTextile World. This type of research is explanatory research, with data collection through a questionnaire,literature study and interviews. Testing is done to the production employees with a sample of 92 people usingproposionate random sampling method. The results showed that organizational culture (X1), andkompensaso (X2) partially or simultaneously affect employee performance (Y) parts production.Organizational culture has the greatest influence in affecting the performance of the employees this can beproved by the results of multiple regression test stating that organizational culture has contributed by 23,4%.While compensation has the smallest influence in affecting the performance of employees with a contributionof 11,4%.